The Model of Oceanic and Marine Circulation INMOM: From Origins to the Present Day - Gusev, A. V.; Diansky, N. A.; Fomin, V. V.; Volodin, E. M.; Zalesny, V. B. (Izvestiya. Atmospheric and oceanic physics, 2025)
The history is presented of the Russian sigma model of oceanic and marine circulation known as INMOM (Institute of Numerical Mathematics Ocean Model). It has been developed for over 50 years, initially at Computing Center, Siberian Branch, Academy of Sciences of the Soviet Union (CC SB АS SU), then at the Institute of Numerical Mathematics, Russian Academy of Sciences (INM RAS). The first version of the model was developed under direct supervision of G.I. Marchuk and was designed for modelling the coupled circulation of the global atmosphere and World Ocean. The main method for solving model equations was the multicomponent splitting technique proposed by Marchuk and evolved by his students and followers. For a half of century, the model’s representation of basic processes, parameterizations, and numerical algorithms were being improved. The novel period in the model’s development proceeded in the late 1990s, when it started to be used as an oceanic component of the INM RAS Earth system model. In the 2000s, the range of its applicability extended essentially. Together with studying the Earth climate system, it started to be implemented for simulating circulation in the World Ocean, as well as individual basins and seas. Currently, the model INMOM is applied for solving a wide range of basic and applied problems concerned with reproducing characteristics of marine and oceanic hydrothermodynamics, including their climatic variability. It is used at the INM RAS; Zubov State Oceanographic Institute (SOI); Shirshov Institute of Oceanology (IO RAS); Hydrometcenter of Russia; V.I. Il’ichev Pacific Oceanological Institute, Far Eastern Branch, Russian Academy of Sciences (POI FEB RAS); and other organizations dealing with study of oceanic and marine hydrothermodynamics. The model is continuing to be evolved by its authors and their colleagues and students.